Insulin Induces Swelling-dependent Activation of the Epidermal Growth Factor Receptor in Rat Liver - Reinehr, Roland (American Society for Biochemistry and Molecular Biology, 2010)
The aim of the study was to analyze whether the proliferative effects of insulin in rat liver involve cross-signaling toward the epidermal growth factor receptor (EGFR) and whether this is mediated by insulin-induced hepatocyte swelling. Studies were performed in the perfused rat liver and in primary rat hepatocytes. Insulin (35 nmol/liter) induced phosphorylation of the EGFR at position Tyr(845) and Tyr(1173), but not at Tyr(1045), suggesting that EGF is not involved in insulin-induced EGFR activation. Insulin-induced EGFR phosphorylation and subsequent ERK1/2 phosphorylation were sensitive to bumetanide, indicating an involvement of insulin-induced hepatocyte swelling. In line with this, hypoosmotic (225 mosmol/liter) hepatocyte swelling also induced EGFR and ERK1/2 activation. Insulin- and hypoosmolarity-induced EGFR activation were sensitive to inhibition by an integrin-antagonistic RGD peptide, an integrin β1 subtype-blocking antibody, and the c-Src inhibitor PP-2, indicating the involvement of the recently described integrin-dependent osmosensing/signaling pathway (Schliess, F., Reissmann, R., Reinehr, R., vom Dahl, S., and Häussinger, D. (2004) J. Biol. Chem. 279, 21294–21301). As shown by immunoprecipitation studies, insulin and hypoosmolarity induced a rapid, RGD peptide-, integrin β1-blocking antibody and PP-2-sensitive association of c-Src with the EGFR. As for control, insulin-induced insulin receptor substrate-1 phosphorylation remained unaffected by the RGD peptide, PP-2, or inhibition of the EGFR tyrosine kinase activity by AG1478. Both insulin and hypoosmolarity induced a significant increase in BrdU uptake in primary rat hepatocytes, which was sensitive to RGD peptide-, integrin β1-blocking antibody, PP-2, AG1478, and PD098059. It is concluded that insulin- or hypoosmolarity-induced hepatocyte swelling triggers an integrin- and c-Src kinase-dependent EGFR activation, which may explain the proliferative effects of insulin.